The trademark legal system in light of the draft Intellectual Property Protection Law for the year 2023 - Abdel Rahman, Massooma (Journal of Legal Sciences, 2025)
Trademarks occupy a central position within the legal framework of intellectual property, serving as a primary tool for protecting goods and services and ensuring their distinctiveness in the marketplace. Their significance increases in the international sphere, particularly when linked to the resolution of commercial disputes through arbitration. In this regard, the 1958 New York Convention represents a cornerstone for the recognition and enforcement of foreign arbitral awards, including those involving trademarks. This research aims to examine the Convention’s impact on strengthening the legal protection of trademarks globally and to explore the extent to which national legal systems align with international obligations. The findings indicate that the Convention not only unified procedural standards but also reinforced investor confidence by ensuring the effective enforcement of trademark-related rights, while still accommodating the legislative specificities of individual states.